2015
DOI: 10.1080/15022250.2015.1114900
|View full text |Cite
|
Sign up to set email alerts
|

How to evaluate cultural impacts of events? A model and methodology proposal

Abstract: The increasing number of events has generated a growing research interest in assessing impacts of the events. So far, most empirical studies have analysed economic impacts, whereas social, political or cultural impacts have been taken into consideration only to a limited extent. The aim of this paper is to propose a conceptual and methodological model to measure and analyse cultural effects of events. This article first examines how social and cultural impacts are conceptualised and analysed by different disci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…Jordi Oliva Codina and Alba Colombo developed a scale based on the Intense Music Experience (IME) proposed by Schäfer. This scale identified the intensity of the emotions felt while listening to music, combined with the Cultural Impact Perception (Colombo, 2016) tool. Experiences were also analysed at the city level by Vladimir Antchak (2018) who looked at how a host city is experienced during the course of large scale events.…”
Section: Introductionmentioning
confidence: 99%
“…Jordi Oliva Codina and Alba Colombo developed a scale based on the Intense Music Experience (IME) proposed by Schäfer. This scale identified the intensity of the emotions felt while listening to music, combined with the Cultural Impact Perception (Colombo, 2016) tool. Experiences were also analysed at the city level by Vladimir Antchak (2018) who looked at how a host city is experienced during the course of large scale events.…”
Section: Introductionmentioning
confidence: 99%
“…Sandell 1998;Newman 2013, Pop andBorza 2016). Moreover, there are also scholars that address the need to measure the social impact of festivals (Caust 2019), events (Colombo 2016;Srakar and Vecco 2017), cultural goods (Klamer 2004) and literature (Belfiore and Bennett 2009). Already in 2008, White and Hede concluded that it was important that cultural organizations have an understanding of their impact, in order to make a link between the impact of the arts and the development of cultural programs.…”
Section: The Need For a New Impact Measurement Frameworkmentioning
confidence: 99%
“…Nonetheless, despite all positive assumptions, there is only limited empirical proof that cultural participation leads to a positive social impact (Colombo 2016;De Beukelaer 2013;Evans 2005;Galloway 2009;Lees and Melhuish 2015;Pop and Borza 2016;Throsby 2003Throsby , 2012. There are some good examples of organizations that focus on this question, such as the Van Gogh Museum in Amsterdam in The Netherlands, who started a four year learning program to gain insight in the impact of their program 'Van Gogh Connects'.…”
Section: Introductionmentioning
confidence: 99%
“…Roberto D. Putnamo teigimu, socialinis kapitalas lemia visuomenės tinklaveiką (socialinių interakcijų ir žmonių tarpusavio asmeninių ryšių tinklą), kuris kuria vertę tiek individui, tiek visuomenei, kaip populiacijai (Putnam, 2002). Per visuomenės tinklaveiką užtikrinama grupės ir pavienių asmenų / kelių grupių tarpusavio interesų derinimas įvairiose veiklose bei bendras išteklių (materialių ir nematerialių) naudojimas derinant skirtingus interesus (Coleman, 1988).…”
Section: įVadasunclassified